2019
DOI: 10.1142/s0129065719500059
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive Therapy Induces Cortical Morphological Alterations in Major Depressive Disorder Revealed with Surface-Based Morphometry Analysis

Abstract: Although electroconvulsive therapy (ECT) is one of the most effective treatments for major depressive disorder (MDD), the mechanism underlying the therapeutic efficacy and side effects of ECT remains poorly understood. Here, we investigated alterations in the cortical morphological measurements including cortical thickness (CT), surface area (SA), and local gyrification index (LGI) in 23 MDD patients before and after ECT. Furthermore, multivariate pattern analysis using linear support vector machine (SVM) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 88 publications
2
37
0
2
Order By: Relevance
“…Although the cognitive impairment was also associated with the insular atrophy, a significant correlation between the insula and depressive symptoms was observed after excluding the effect of the cognitive impairment. The result strongly indicated that the insula is vital in the modulation of emotion, which is consistent with previous research that demonstrated insular structures to be abnormal in patients with depressive disorder (Hayata et al, 2015;Ambrosi et al, 2017;Cooper et al, 2019;Whitton et al, 2019;Xu et al, 2019). The insula, as a vital visceral sensory node, is significantly correlated with somatic symptoms in depressed patients (Zu et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Although the cognitive impairment was also associated with the insular atrophy, a significant correlation between the insula and depressive symptoms was observed after excluding the effect of the cognitive impairment. The result strongly indicated that the insula is vital in the modulation of emotion, which is consistent with previous research that demonstrated insular structures to be abnormal in patients with depressive disorder (Hayata et al, 2015;Ambrosi et al, 2017;Cooper et al, 2019;Whitton et al, 2019;Xu et al, 2019). The insula, as a vital visceral sensory node, is significantly correlated with somatic symptoms in depressed patients (Zu et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…The electroconvulsive therapy (ECT) is one of the most potent and rapid way to relieve depression for treatmentresistant MDD patients, leading to remission in~50-70% of such patients 20,21 . To date, many previous studies were performed to explore the structural and functional alterations related to the ECT [22][23][24][25][26][27][28][29] , the mechanisms underlying the therapeutic efficacy and side effects of ECT in MDD patients is still controversial. Since the emotion dysregulation is thought to be one of the core symptoms and underlying mechanisms of MDD, exploring the organization of the ERN and how it is modulated by the ECT is therefore crucial to uncover the mechanisms of ECT.…”
Section: Introductionmentioning
confidence: 99%
“…Depression presents with sorrow, guilt, fatigue, low self-worth, irregular sleep/appetite, loss of interest, and low concentration (Xu J. et al, 2019;Olejarczyk et al, 2020). Commonly, these symptoms persist in the long term and recur easily.…”
Section: Depressive Disordermentioning
confidence: 99%